Two-sided illumination in rigorous coupled-wave analysis applied to the 4π-microscope - Junker, André; Brenner, Karl-Heinz (Journal of the Optical Society of America. A, Optics, image science, and vision, 2017)
We apply the rigorous coupled-wave analysis (RCWA) to the simulation of 4π-microscopy. To achieve this, the concept of structured illumination [J. Opt. Soc. Am. A31, 2385 (2014)] is combined with the idea of coherent two-sided light incidence. We show how the latter can be integrated into the framework of the RCWA. Furthermore, we derive how light sources with different polarization types, such as linear, radial, or azimuthal polarization, can be realized in a general form. We combine these techniques to simulate two coherent counterpropagating converging beams incident upon a sample, as in 4π-microscopy.